Angina bullosa hemorrhagica: A case report and review of the literature - Hassan El-Awour; Kinda Allaham; Mohammed Inam Ullah Khan (Oral and Maxillofacial Surgery Cases)
Here we present a case of Angina Bullosa Hemorrhagica (ABH) and review the literature highlighting its features, differentiation diagnosis from similar lesions, management considerations, and treatment options. Furthermore, we present a treatment algorithm for managing cases of this rare disorder. ABH lesions commonly manifest on the palate, tongue, buccal mucosa, lips, the floor of the mouth, and uvula. ABH range in size, from 4 to 30 mm in diameter. ABH lesions are generally self-limiting and resolve within a few days without scarring. Management recommendations may include supportive therapy for small lesions, incision for large bulla and continued palliative therapy using mouthrinses and analgesics. Though, ABH is a rare disorder, general dental practitioners ought to be aware of it. This report provides guidance on diagnosis, management and investigations in hopes to avoid ill-informed or unnecessary treatments.